Student nurses' practices and willingness to teach relatives breast self-examination in Nigeria - Joel O. Aluko; Olayinka A. Onasoga; Regis R. Marie Modeste; Odinaka B. Ani (AOSIS, 2024)
Background: Breast cancer is the most common cancer and the leading cause of cancer-related death for women worldwide. Breast self-examination (BSE) is an essential, low-cost, and simple tool for detecting breast cancer early. Employing the idea of 'charity begins at home' by involving student nurses in teaching BSE to relatives will improve early detection. Aim: To assess nursing students' practice and willingness to teach BSE to their relatives. Setting: A college of nursing and midwifery in one state under North-Central Nigeria. Methods: A cross-sectional descriptive design was employed. Through incidental sampling technique 197 respondents were selected from the first to the third year. Data were collected using a structured questionnaire. Descriptive and inferential analyses, with a p-value of 0.05 were conducted. Results: Respondents indicated where they learned about BSE. There were 98.5% respondents who had heard about BSE, and 89.8% of them had good practice of BSE. However, a quarter did not teach BSE to relatives. There were no statistically significant associations noted. Conclusion: Most of the nursing students were aware of BSE and knew how to perform it, although a quarter did not teach BSE to their relatives. Therefore, it may be necessary to sensitise nurses to cultivate the habit of teaching BSE to relatives and women in the community. Contribution: It is crucial to provide nurses with the skills and knowledge required to carry out BSE effectively, as well as teach women how to perform it on themselves, to improve breast cancer detection rates in Nigeria.